NOSOCOMIAL UROPATHOGENS AND THEIR ANTIBIOTIC SENSITIVITY PATTERNS IN A TERTIARY REFERRAL TEACHING HOSPITAL IN RAWALPINDI, PAKISTAN - Khan, Basharat Ali; Saeed, Sami; Akram, Adeel; Khan, Faraz Basharat; Nasim, Amjad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Nosocomial urinary tract infections (NUTIs) are by definition not present at admission of a patient and are acquired during hospitalisation. The objective of this study was to study the uropathogens and their antibiotic sensitivity patterns in hospital acquired urinary tract infections presenting in a teaching hospital. Methodology: It was a retrospective descriptive study carried out at the Department of Pathology, Fauji Foundation Hospital, Rawalpindi, Pakistan, during the year 2009. Reports of urine culture and sensitivity performed during one year were retrospectively studied with a view to document various isolates and their antimicrobial sensitivity. Results: Out of a total number of 1204 urine cultures submitted, 246 were found to have nosocomial urinary tract infections. Over all prevalence of nosocomial urinary tract infection in the examined reports was 20.43%. Conclusion: Nosocomial Urinary tract infections are common. Gram negative bacilli are most frequent uropathogens and are resistant to commonly used antibiotics. Fosfomycin followed by Gentamycin and Cefotaxime were the most effective antibiotics. Keywords: uropathogens, antibiotics, urine, culture, sensitivity